Epistatic Transcription Factor Networks Differentially Modulate Arabidopsis Growth and Defense. Issue 2 (1st February 2020) - Li, Baohua; Tang, Michelle; Caseys, Céline; Nelson, Ayla; Zhou, Marium; Zhou, Xue; Brady, Siobhan M; Kliebenstein, Daniel J
Abstract: How a plant regulates the relationship between plant growth and plant defense is critical for understanding plant fitness or yield. Yet, little about the required complex underlying interactions are understood.... Plants integrate internal and external signals to finely coordinate growth and defense for maximal fitness within a complex environment. A common model suggests that growth and defense show a trade-offs relationship driven by energy costs. However, recent studies suggest that the coordination of growth and defense likely involves more conditional and intricate connections than implied by the trade-off model. To explore how a transcription factor (TF) network may coordinate growth and defense, we used a high-throughput phenotyping approach to measure growth and flowering in a set of single and pairwise mutants previously linked to the aliphatic glucosinolate (GLS) defense pathway. Supporting a link between growth and defense, 17 of the 20 tested defense-associated TFs significantly influenced plant growth and/or flowering time. The TFs' effects were conditional upon the environment and age of the plant, and more critically varied across the growth and defense phenotypes for a given genotype. In support of the coordination model of growth and defense, the TF mutant's effects on short-chain aliphatic GLS and growth did not display a simple correlation. We propose that large TF networks integrate internal and external signals and separately modulate growth and the accumulation of the defensive aliphatic GLS.